Planning and analyzing clinical trials with composite endpoints - Rauch, Geraldine (Springer, 2019)
Intro -- Preface -- Contents -- Part I General Introduction to Composite Endpoints -- 1 Definition and Rationale -- 1.1 Definitions and Types of Composite Endpoints -- 1.1.1 Composite Binary Event Endpoints -- 1.1.2 Composite Time-to-First-Event Endpoints -- 1.1.3 A Note on Clinical Scores -- 1.2 Rationale for the Use of Composite Endpoints -- 1.2.1 Augmenting Power -- 1.2.2 Avoiding Multiplicity -- References -- 2 Challenges of Composite Endpoints -- 2.1 Uncertainties in the Planning Stage -- 2.2 Interpretation of Results -- 2.3 Competing Risks as a Source of Bias -- 2.4 Follow-Up Beyond the First Event -- References -- 3 Guideline View: Recommendations and Requirements -- 3.1 Guidelines Related to Composite Endpoints -- 3.2 Guideline Recommendations -- 3.3 Beyond the Guidelines: Open Issues -- References -- 4 Clinical Trial Examples -- 4.1 The Osteoporosis Trial -- 4.2 The MOMS Trial -- 4.3 The OMEGA Trial -- 4.4 The RENAAL Trial -- 4.5 The DREAM Trial -- 4.6 The CAPRICORN Trial -- 4.7 The LIFE Trial -- References -- Part II Confirmatory Test Problem for a Single (Composite) Endpoint -- 5 The Single-Stage Design -- 5.1 Binary Endpoints -- 5.1.1 Test Problem -- 5.1.2 Test Statistics -- 5.1.3 Sample Size Calculation -- 5.1.3.1 Standard Sample Size Calculation -- 5.1.3.2 Robust Sample Size Calculation -- 5.2 Time-to-Event Endpoints Under Proportional Hazards -- 5.2.1 Test Problem -- 5.2.2 Test Statistics -- 5.2.3 Sample Size Calculation -- 5.2.3.1 Standard Sample Size Calculation -- 5.2.3.2 Robust Sample Size Calculation -- 5.3 Time-to-Event Endpoints for Non-proportional Hazards -- 5.3.1 Test Problem -- 5.3.2 Test Statistics -- 5.3.3 Sample Size Calculation -- 5.4 Recurrent Event Analysis -- References -- 6 Group-Sequential and Adaptive Designs -- 6.1 Stage-Wise Local Levels -- 6.1.1 Choice of Stage-Wise Local Levels.
Description based on publisher supplied metadata and other sources